PELATIHAN BATIK TULIS ARIMBI SEBAGAI VALUE CO-CREATION KAMPOENG DJAWI WONOSALAM - Fatma Ayu Nuning; Andhika Mayasari; Sumarsono; Nur Muflihah (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2022)
Abstract: Local wisdom can support in overcoming various problems that exist in the community. Local wisdom which is part of cultural heritage has the potential to be used as a development resource, especially in rural areas. In this community service activity, the focus is on local wisdom in Wonosalam, Jombang. The government of Jombang Regency also encourages the development of rural tourism in which Wonosalam is the pre-eminent area. The sustainability of tourist villages is always being developed so that it is necessary to add value/character (value co-creation) to tourist villages in the Wonosalam area. Batik which is the heritage of the Indonesian nation and the heritage of Humanity for Oral and Intangible Culture (Masterpice of the Oral and Intangible Herritage of Umanity) has value and has been recognized internationally. Based on direct observations of the movement of tourists in Wonosalam, an important conclusion can be drawn, namely the need to collaborate on the development of typical Jombang batik as local wisdom that is able to provide value to support the competitiveness of tourist villages in Wonosalam. The process of hand-drawn batik as a service as a possible creative part will continue to grow. To achieve this, we first examine the batik in Jombang. Then analyze the Jombang batik motif, where the arimbi batik motif is the superior motif. Our service approach is adopted from Participatory Action Research with the perspective of preserving culture and local wisdom. Tourist village visitors can enjoy the batik process, especially the Jombang batik motif/arimbi motif as a value co-creationKeywords: Batik, Local_Wisdom, EmpowermentAbstrak: Kearifan lokal membantu kita mengatasi berbagai masalah yang sebenarnya ada di masyarakat kita. Kearifan lokal sebagai bagian dari warisan budaya dapat dugunakan sebagai salah satu sumber pembangunan terutama di daerah pedesaan. Pada program pengabdian ini berfokus pada kearifan lokal Wonosaram. Pemerintah Kabupaten Jombang juga sedang menggalakkan pengembangan desa wisata, dimana Wonosalam merupakan salah satu daerah unggulannya. Keberlanjutan desa wisata terus dikembangkan, dan perlu adanya nilai tambah desa wisata yang ada di wilayah Wonosalam. Batik, warisan nasional Indonesia dan warisan budaya takbenda lisan umat manusia (masterpiece of oral intangible heritage of human), bernilai dan diakui secara internasional. Pengamatan terhadap pergerakan wisatawan di Wonosaram dapat menghasilkan kesimpulan penting, kita perlu bekerjasama dalam pengembangan batik khas Jombang sebagai kearifan lokal yang dapat memberikan nilai tambah untuk menjadikan desa wisata Wonosalam lebih berdaya saing. Proses batik tulis tangan sebagai layanan bagian kreatif dapat dikembangkan. Untuk mencapainya pertama-tama kami mengkaji batik yang ada di Jombang. Kemudian menganalisis motif batik Jombang, dimana batik motif arimbi sebagai motif unggulan.. Pendekatan layanan kami didasarkan pada penelitian tindakan partisipatif dalam hal melestarikan budaya dan kearifan masyarakat. Pengunjung desa wisata dapat menikmati proses layanan membatik, khususnya motif batik Jombang/motif Arimbi sebagai value co-creation.Kata kunci: Batik,Kearifan_Lokal,Pemberdayaan